The hate next door: why white supremacists are all around us - and how to spot them - Browning, Matson (Sourcebooks, 2024)
"For more than twenty-five years, Browning has been infiltrating, documenting, and disrupting white supremacy movements from the inside, gaining an intimate vantage point to the KKK, skinheads, border militias, Proud Boys, and other White Power groups, as they organized and grew, their ranks alarmingly including police force and military veterans. Together with his intrepid wife, Tawni, he adopted fake IDs and ideologies, seeking the arrest of its participants--none more so than J.T. Ready, a neo-Nazi who took "hunting trips" for border migrants while gaining mainstream acceptance as a political candidate--and terrorizing Browning's family. What others dismissed as fringe groups, Browning quickly recognized as large and interconnecting organizations permeating into every facet of American society, effectively spreading their dangerous and repugnant rhetoric at unprecedented speeds. Today, after the violent storming of the Capitol on January 6th, the threat posed by these toxic organizations can no longer be ignored by the public at large. In this imperative and gripping narrative, Browning gives readers the inside story of modern-day White supremacy in America in all of its ugly variation. Following his dramatic, high-stakes attempts to take down powerful White supremacists, the torment he faced whilst working undercover, and his eventual creation of the international Skinhead Intelligence Network, The Hate Next Door is a riveting, enlightening, and essential look at the what, where, when, and why of white supremacist groups, how to identify them, and why we must all do everything in our power to fight against them."--